Phytotelmata colonization in bamboo (Guadua sp.) culms in northeast Argentina - Campos, Raul Ernesto (2015)
This study aimed to determine the susceptibility of stumps andinternodes of bamboos to colonization by different types ofmacroinvertebrates and the formation of communities of differentcomplexity. Semi-controlled field studies were carried out in asubtropical area of Argentina to analyse community structure,species richness of the aquatic macroinvertebrate communitiesand co-occurrences of predators and prey to delineate the foodwebs. Water-filled bamboos were sampled every season during ayear by removing, without replacing, all water and macroinvertebrates.This study shows that the variation in the morphology ofthe container provides different resources, leading to segregationof species per container type, and allowing each of them toestablish aquatic communities with differences in diversity. TheDiptera was best represented in the communities of bamboos,where Culicidae showed the highest species richness andCeratopogonidae were the most abundant numerically. Eleventaxa were present in both phytotelmata, 12 were unique in internodesand 13 in stumps. The community in internodes was composedof 21 taxa where mosquitoes were represented bySabethini and Toxorhynchitini. By contrast, stumps were colonizedby 24 taxa and Ceratopogonidae were numerically dominant.Regarding food webs established in stumps and internodes, nodifferences in length were found, except for the species thatplayed equivalent roles in each of the studied phytotelmata.